ANALISIS KADAR TIMBAL (Pb) PADA JAJANAN PINGGIRAN JALAN Ir. H. JUANDA KOTA JAMBI - Marhadi Marhadi; Anggrika Riyanti (Universitas Batanghari, 2018)
Lead Content Analysis (Pb) On Snack Road Ir. H. Juanda City Jambi increasingly proliferation of street vendors snack on the street where the activity is quite crowded, allowing snacks that are sold can be contaminated by lead (Pb) coming from motor vehicle fumes. This study aims to determine the content of lead on street snacks and compared with the maximum limit of lead food in snack foods that have been determined by the Director General of POM in the decision of Director General of POM Number HK.00.06.1.52.4011 Year 2009 on the maximum limit of metal contamination in food that is 0,25 ppm. This research is a descriptive research that gives a picture of lead content in snack. The study was conducted on traders selling fried foods at Street H. Juanda Jambi City. Sampling using total sampling technique where for each place of sale taken three kinds of fried foods such as fried bananas, tofu contents and bakwan. Examination of laboratory test of Environment Department (DLH) Province Jambi Year 2017 got big parameter of S02 equal to 19.5 μg/nm3 whereas standard quality standard set PP. 41 of 1999 on the ambient air quality of 900 μg/nm3, for the parameter N02 of 23.0 μg/nm3, while the standard quality standard set PP. 41 of 1999 on ambient air quality of 400 μg/nm3, for lead parameters (Pb) with the result 0.082 μg/nm3, while the standard quality standard established PP. 41 year 1999 About ambient air quality of 2 μg/nm3 and dust parameter with result 80 μg/nm3 while standard quality standard set PP. 41 of 1999 on ambient air quality of 230 μg/nm3. The content of timbale in banana snack food is 0,0850%, for food bakwan is 0.0008% and for food tofu content is 0,1505% so it has not exceed the maximum limit of metal contamination in food which has been determined by Dirjen POM in decision of Dirjen POM Number HK.00.06.1.52.4011 Year 2009 is 0.25 ppm.Keywords : Ambient Air Quality, Lead (Pb), snack food